Programming teaching with robotic support for people who are visually impaired: a systematic review - Oliveira, Juliana Damasio; Jurak, Darlan A.; Bittencourt, Robson F.; Campos, Márcia de B.; Amory, Alexandre M. (Anais do Simpósio Brasileiro de Informática na Educação (SBIE); 2019: Anais do XXX Simpósio Brasileiro de Informática na Educação, 2019)
Robotics has been used to draw students’ attention to computing and engineering. Unfortunately, most of the hardware and software features used to teach programming and robotics are not suitable for students who are visually impaired. Most programming environments are highly visual interfaces which makes them inaccessible for the visually impaired. This paper aims to present the studies regarding the use of robotics for the teaching of programming for people who are visually impaired that were published between 2016 and 2019, through a systematic literature review. As a result, we identified the teaching methodologies, the robotics and programming kits used, the good practices and difficulties faced in programming teaching with robotic support.